A Review Paper on Renewable Energy (International Journal of Food and Nutritional Sciences, 2022)
Renewable energy is obtained from organic renewable resources that are replenished on a humans timescale. Renewable energy sources include sunshine, winds, rain, tides, tides, and subterranean heat. This article examines renewable energy in general, as well as the many forms of renewable energy, as well as the benefits and drawbacks of renewable energy. Renewable energy is essential to our civilization's level of life and underpins all other areas of our economy. Renewable energy technologies offer a steady supply of clean energy produced from renewable resources such as the sunlight, wind, soil, and plants. Almost every location of the U.s and the globe has some kind of renewable resource. Renewable energy sources now account for roughly 10% of total energy usage in the US, with hydropower and traditional bioenergy sources providing for the bulk of this. In a rising number of industries, renewable energy sources such as wind, solar, biomass, and thermal are growing more cost-effective, and they are making significant progress toward broader commercialization.